Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.2337/diabetes.50.2007.s58
|View full text |Cite
|
Sign up to set email alerts
|

beta-cell apoptosis: stimuli and signaling.

Abstract: Pancreatic ␤-cells are sensitive to a number of proapoptotic stimuli. Thus, apoptosis is an important part of the physiological neonatal remodeling of the endocrine pancreas, and a number of pathological stimuli involved in type 1 and type 2 diabetes have been shown to elicit ␤-cell apoptosis. Factors of relevance to type 1 diabetes include proinflammatory cytokines, nitric oxide, and reactive oxygen species as well as Fas ligand. Recent findings that free fatty acids, glucose, sulfonylurea, and amylin cause ␤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
165
0
9

Year Published

2002
2002
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(177 citation statements)
references
References 46 publications
(49 reference statements)
3
165
0
9
Order By: Relevance
“…As demonstrated in several studies (52)(53)(54), the supply of oxygen in both the early posttransplant period and long-term is largely limited at the intraportal transplantation site, but is nevertheless crucial for islet survival and function. Islets exposed to chronic hypoxia are especially susceptible to hypoxia-mediated inflammatory reactions, oxidative stress, and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated in several studies (52)(53)(54), the supply of oxygen in both the early posttransplant period and long-term is largely limited at the intraportal transplantation site, but is nevertheless crucial for islet survival and function. Islets exposed to chronic hypoxia are especially susceptible to hypoxia-mediated inflammatory reactions, oxidative stress, and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from direct killing of beta cells by autoreactive T cells, another possible mechanism of beta cell loss in autoimmune type 1 diabetes may be cytokine-induced apoptosis [33,34]. Recently, it was reported that GLP-1 and other growth factors have an anti-apoptotic effect [11][12][13]35].…”
Section: Discussionmentioning
confidence: 99%
“…To distinguish between these two possibilities, we first investigated whether UCP2 deficiency in islets may affect cytokine-induced ␤-cell death, the major death signal for ␤-cells (14,15). A mechanism by which cytokines impair ␤-cell function and, in part, mediate ␤-cell death is by induction of the expression of the inducible form of NO synthase (iNOS) and thus NO production (16)(17)(18). We measured NO production of islets isolated from Ucp2-WT and Ucp2-KO mice treated or not with IL-1␤ and IFN-␥ for 48 h, as previously described (19).…”
Section: Lack Of Ucp2 In ␤-Cells Does Not Affect Mlds-induced Diabetesmentioning
confidence: 99%